Feynmanova raglja - Mati Djuraki, Urša (Matrika, 2024)
Feynman’s ratchet is a microscopic heat engine propelled by the collisions of molecules. It first appeared as a thought experiment and is still interesting today as a model for molecular motors and pumps. The first experimental realisation of Feynman’s ratchet was conducted a few years ago. The first part of this article considers the heat engine in the original form as imagined by Feynman. The second part describes the experimental realisation.
Keywords: Feynman’s ratchet; Feynmanova raglja; heat engines; termodinamika; thermodynamics; toplotni stroji